An in vitro study on the anti-bacterial effect of xylitol on streptococcus mutans - Ablaza, J.; Aguila, C.
Streptocuccus mutans cocci were isolated, maintained and grown in Brewer's tioglycollate broth, at a density of 1.5 x 10 cells/ml. The organism was subjected to different concentrations of xylitol ranging from 125 mg/ml to 2000 mg/ml, doubling in each successive tube. In the tube deletion method, the minimum inhibitory concentration (MIC) was 250 mg/ml. There was 100% reduction of turbidity in the 2000 mg/ml tube. In the disc method, xylitol, at exhibited zones of inhibition or restricted growth.
Keywords: Streptococcus mutans; Xylitol; Disc method; Tube dilution method